“Hi, Madam, I have a small question.” Teaching QM online: Guide to a successful cross-cultural master-course - Ryen, Anne (Qualitative Sociology Review, 2009)
A few years ago Centre of Development Studies at my Faculty, Faculty of Economics and Social Sciences, started an online Master’s Programme in Development Management. The programme was implemented by a network of universities from the North (University of Agder/UiA) and the South (Sri Lanka, Tanzania, Ethiopia, Uganda, Ghana) recruiting students from across the world. The evaluation is very positive characterising it as a big success. I will now look into one particular element of this study, teaching the qualitative methodology (QM) courses with a special focus on the South context. Each course QM included has been sectioned into modules based on a variety of students` activities including student-student and student-tutor/teacher interaction, plus a number of hand-ins across topics and formats. Evaluation of the students` performance is based on both online group activity and written material submitted either into the individual or the group portfolio. My focus is twofold. First, how did we teach qualitative methodology and how did that work? Second, what about the contemporary focus on neo-colonial methodology and our QM courses? In a wider perspective the study is part of foreign aid where higher education is a means to transfer competence to the South. As such this study works to enable and to empower people rather than being trapped in the old accusation of sustaining dependency (Asad 1973, Ryen 2000 and 2007a). This study then is embedded in a wider North-South debate and a highly relevant illustration of the potentials, success and hazards, inherit in teaching QM.